Β-Sitosterol Protects against Myocardial Ischemia/Reperfusion Injury via Targeting PPARγ/NF-κB Signalling. (28th March 2020) - Lin, Fengxia; Xu, Luhua; Huang, Meizhu; Deng, Bin; Zhang, Weiwei; Zeng, Zhicong; Yinzhi, Song
Abstract : Myocardial ischemia/reperfusion (I/R) injury is a clinically severe complication, which can cause high rates of disability and mortality particularly in patients with myocardial infarction, yet the molecular mechanisms underlying this process remain unclear. This study aimed to explore the protective effects of β -sitosterol against myocardial I/R injury and to elucidate the underlying molecular mechanisms. Our results showed that hypoxia/reoxygenation (H/R) treatment suppressed cell viability, induced cell apoptosis and reactive oxygen species production, increased caspase-3 and -9 activities, upregulated caspase-3 and -9 protein expressions, downregulated the Bcl-2 protein expression, and reduced the mitochondrial membrane potential. β -Sitosterol treatment attenuated H/R-induced cardiomyocyte injury. Moreover, β -sitosterol treatment counteracted the inhibitory effects of H/R treatment on the peroxisome proliferator-activated receptor gamma (PPARγ) expression and enhanced effects of H/R treatment on the NF-κB expression in cardiomyocytes. Furthermore, inhibition of PPARγ impaired the protective actions of β -sitosterol against H/R-induced cardiomyocyte injury. In the I/R rats, β -sitosterol treatment reduced the myocardial infarcted size and apoptosis, which was attenuated by the inhibition of PPARγ. In conclusion, our results demonstrate that β -sitosterol protected against in vitro H/R-induced cardiomyocyte injury and in vivo myocardial I/R injury. The β -sitosterol-mediated cardioprotective effects may involve the modulation of PPAR γ /NF- κ B signalling during myocardial I/R injury. Further studies are required to further explore the clinical application of β -sitosterol in the myocardial I/R injury.